Menu Engineering Strategy in Increasing Menu Popularity and Profitability within the Food and Beverage Services of Sheraton Grand Jakarta Gandaria City Hotel - Noval Adithya Rahman; Lise Asnur; Yogi Hidayat (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This inquiry conceptualizes and evaluates the implementation of Menu Engineering strategy in increasing menu popularity and profitability within the Food and Beverage services of Sheraton Grand Jakarta Gandaria City Hotel. The empirical urgency of this research stems from significant operational anomalies observed in field sales data, wherein specific menu items dominate sales volume yet yield substandard contribution margins, while high-profit variants experience demand stagnation. To address this misalignment, this descriptive quantitative study adopts the Kasavana & Smith matrix model to systematically classify the product portfolio into four strategic quadrants: Star, Plowhorse, Puzzle, and Dog. The primary datasets analyzed comprise authentic transactional records legally extracted from the Micros Oracle Point of Sales (POS) system for a full year from January to December 2025. The empirical findings throughout the year reveal the performance distribution of culinary products, such as the Angus Burger and Truffle Fries which consistently secure superior quadrant placement, whereas several local dishes require immediate production cost restructuring. Consequently, this study formulates data-driven managerial recommendations, including rigorous portion control standardization for the Plowhorse segment, the optimization of suggestive selling techniques to stimulate the Puzzle category, and inventory rationalization to mitigate material waste in the Dog quadrant, thereby ensuring the sustainability of the hotel's operational gross profit.